A global analysis of CO2 and non-CO2 GHG emissions embodied in trade with Belt and Road Initiative countries. Issue 1 (16th December 2020) - Hou, Jing; Deng, Xu; Springer, Cecilia Han; Teng, Fei
ABSTRACT: Introduction : The Belt and Road Initiative (BRI) is an important cooperative framework that increasingly affects the global economy, trade, and emission patterns. However, most existing studies pay insufficient attention to consumption-based emissions, embodied emissions, and non-CO2 greenhouse gases (GHGs). This study constructs a GHG emissions database to study the trends and variations in production-based, consumption-based, and embodied emissions associated with BRI countries.Outcome : We find that the per capita GHG emissions of BRI countries are lower than the global average but show significant variation within this group. We also find that trade-embodied emissions between BRI countries and China are growing. As a group, BRI countries are anet exporter of GHGs, with a global share of net export emissions of about 20%. In 2011, nearly 80% of GHG export emissions from BRI countries flowed to non-BRI countries, and nearly 15% flowed to China; about 57% of GHG import emissions were from non-BRI countries, and about 38% were from China.Conclusion : Therefore, this study concludes that the BRI should be used to coordinate climate governance to accelerate and strengthen the dissemination and deployment of low-emissions technologies, strategies, and policies within the BRI so as to avoid a carbon-intensive lock-in effect.